Industrial Clustering and Sectoral Growth: a Network Dynamics Approach - Jo\~ao Carlos Ferreira Lopes; Tanya Vianna de Araújo; Jo\~ao Dias; Jo\~ao Ferreira do Amaral (European Regional Science Association (ERSA), 2011)
Cluster analysis has been widely used in an Input-Output framework, with the main objective of uncover the structure of production, in order to better identify which sectors are strongly connected with each other and choose the key sectors of a national or regional economy. There are many empirical studies determining potential clusters from interindustry flows directly, or from their corresponding technical (demand) or market (supply) coefficients, most of them applying multivariate statistical techniques. In this paper we follow a different strategy. Since it is expected that strongly (interindustry) connected sectors share a similar growth and development path, we will try to uncover clusters from sectoral dynamics, by applying a stochastic geometry technique, based on the yearly distances of industry outputs. An application is made, comparing these growth based cluster templates with interindustry based ones, using Portuguese input-output data. Identifying regional clusters and its dynamics can be a useful extension of the methods proposed in this paper.
Keywords: 330